Community Based Tourism Dalam Pengembangan Pariwisata Di Desa Akah, Kecamatan Klungkung, Kabupaten Klungkung - Lewi Asih, Ni Wayan; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
Akah Village has great potential for developed into tourist destination both in terms of natural resources and the socio cultural conditions of the local people. However, this high potential cannot be developed optimally because of the limited budget and infrastructure. In addition, level of local community participation in tourism development in Akah Village is still far from what was expected. This research using a qualitative descriptive method studied using sustainable tourism development theory with the Community Based Tourism approach by Yaman and Mohd. Based on the study using the CBT approach, the results of the research show that there are several indicators that have worked well such as support from the government, strengthening local institutions, and sustainable use of local resources, while there are several other indicators that have worked but are not good, such as participation from the stakeholders, equitable benefit sharing and linkages between regional and national levels. Keywords: CBT, sustainable tourism, village potential, community participation.